Estimated Burden of Community-Onset Respiratory Syncytial Virus–Associated Hospitalizations Among Children Aged <2 Years in the United States, 2014–15. (23rd December 2019) - Arriola, Carmen S; Kim, Lindsay; Langley, Gayle; Anderson, Evan J; Openo, Kyle; Martin, Andrew M; Lynfield, Ruth; Bye, Erica; Como-Sabetti, Kathy; Reingold, Arthur; Chai, Shua; Daily, Pam; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of hospitalizations in young children. We estimated the burden of community-onset RSV-associated hospitalizations among US children aged <2 years by extrapolating rates of RSV-confirmed hospitalizations in 4 surveillance states and using probabilistic multipliers to adjust for ascertainment biases. Methods: From October 2014 through April 2015, clinician-ordered RSV tests identified laboratory-confirmed RSV hospitalizations among children aged <2 years at 4 influenza hospitalization surveillance network sites. Surveillance populations were used to estimate age-specific rates of RSV-associated hospitalization, after adjusting for detection probabilities. We extrapolated these rates using US census data. Results: We identified 1554 RSV-associated hospitalizations in children aged <2 years. Of these, 27% were admitted to an intensive care unit, 6% needed mechanical ventilation, and 5 died. Most cases (1047/1554; 67%) had no underlying condition. Adjusted age-specific RSV hospitalization rates per 100 000 population were 1970 (95% confidence interval [CI], 1787 to 2177), 897 (95% CI, 761 to 1073), 531 (95% CI, 459 to 624), and 358 (95% CI, 317 to 405) for ages 0–2, 3–5, 6–11, and 12–23 months, respectively. Extrapolating to the US population, an estimated 49 509–59 867 community-onset RSV-associated hospitalizations among children aged <2 years occurred during the 2014–2015 season. Conclusions: Our findings highlight the importance of RSV as a cause of hospitalization, especially among children aged <2 months. Our approach to estimating RSV-related hospitalizations could be used to provide a US baseline for assessing the impact of future interventions.